Meanings generated while using algebraic-like formalism to construct and control animated models - C Kynigos; G Psycharis; F Moustaki (International Journal for Technology in Mathematics Education, 2010)
This paper reports on a design experiment conducted to explore the construction of meanings by 17 year old students, emerging from their interpretations and uses of algebraic like formalism. The students worked collaboratively in groups of two or three, using MoPiX, a constructionist computational environment with which they could create concrete entities in the form of models by using equations and animate them to link the equations formalism to the produced visual representation. Our aim was to further study the ways in which the use of formalism in constructionist environments can create contexts for the emerging of mathematical meanings. Some illustrative examples of two groups of students work indicate the potential of the activities and tools for expressing and reflecting on the mathematical nature of the available formalism. We particularly focused on the students engagement in reification processes, i.e. making sense of structural aspects of equations, involved in conceptualising them as objects that underlie the behaviour of the respective models